Medium. The fifth season [videorecording (DVD)]. - Arquette, Patricia, 1968-; Weber, Jake, 1964-; Sandoval, Miguel, 1951-; DuBois, Allison (Paramount Pictures, 2008)
Allison and her family's world is turned upside down after her abilities to talk to dead people, see into the future, and read people's thoughts are publicly exposed. The results cause major changes in both her professional and personal life.